Codesign and development of a primary school based pathway for child anxiety screening and intervention delivery: a protocol, mixed-methods feasibility study - Tamsin Ford; Alastair Gray; Cathy Creswell; Victoria Williamson; Obioha Ukoumunne; Falko Sniehotta; Mara Violato; Ian Macdonald; Paul Brown; Paul Stallard; Michael Larkin; Tessa Reardon; et al. (BMJ Open)
Introduction Anxiety difficulties are among the most common mental health problems in childhood. Despite this, few children access evidence-based interventions, and school may be an ideal setting to improve children’s access to treatment. This article describes the design, methods and expected data collection of the Identifying Child Anxiety Through Schools – Identification to Intervention (iCATS i2i) study, which aims to develop acceptable school-based procedures to identify and support child anxiety difficulties.Methods and analysis iCATS i2i will use a mixed-methods approach to codesign and deliver a set of procedures—or ‘pathway’—to improve access to evidence-based intervention for child anxiety difficulties through primary schools in England. The study will consist of four stages, initially involving in-depth interviews with parents, children, school staff and stakeholders (stage 1) to inform the development of the pathway. The pathway will then be administered in two primary schools, including screening, feedback to parents and the offer of treatment where indicated (stage 2), with participating children, parents and school staff invited to provide feedback on their experience (stages 3 and 4). Data will be analysed using Template Analysis.Ethics and dissemination The iCATS i2i study was approved by the University of Oxford’s Research Ethics Committee (REF R64620/RE001). It is expected that this codesign study will lead on to a future feasibility study and, if indicated, a randomised controlled trial. The findings will be disseminated in several ways, including via lay summary report, publication in academic journals and presentation at conferences. By providing information on child, parent, school staff and other stakeholder’s experiences, we anticipate that the findings will inform the development of an acceptable evidence-based pathway for identification and intervention for children with anxiety difficulties in primary schools and may also inform broader approaches to screening for and treating youth mental health problems outside of clinics.